2020
DOI: 10.1101/2020.07.17.209023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood-derived mitochondrial DNA copy number is associated with gene expression across multiple tissues and is predictive for incident neurodegenerative disease

Abstract: Mitochondrial DNA copy number (mtDNA-CN) can be used as a proxy for mitochondrial function and is associated with a number of aging-related diseases. However, it is unclear how mtDNA-CN measured in blood can reflect risk for diseases that primarily manifest in other tissues. Using the Genotype-Tissue Expression Project, we interrogated the relationships between mtDNA-CN measured in whole blood and gene expression from whole blood as well as 47 additional tissues. We evaluated associations between blood-derived… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…chronic kidney disease 13 , heart failure 11 , and diabetes 75 ). Also consistent with this finding is recent work demonstrating that mtDNA-CN measured in blood is associated with mtRNA expression across numerous non-blood tissues, suggesting a link between mitochondrial function measured in blood and other tissues 76 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…chronic kidney disease 13 , heart failure 11 , and diabetes 75 ). Also consistent with this finding is recent work demonstrating that mtDNA-CN measured in blood is associated with mtRNA expression across numerous non-blood tissues, suggesting a link between mitochondrial function measured in blood and other tissues 76 .…”
Section: Discussionsupporting
confidence: 87%
“…We were able to identify a substantial proportion of the genes involved in mtDNA depletion syndromes (7/16, p = 3.09 × 10 −15 for enrichment), including TWNK, TFAM, DGUOK, MGME1, RRM2B, TYMP , and POLG . mtDNA depletion syndromes can be broken down into 5 subtypes based on their constellation of phenotypes 65 , and with the exception of cardiomyopathic subtypes (associated with mutations in AGK and SLC25A4 ), we were able to identify at least 1 gene from the other 4 subtypes, suggesting that our mtDNA-CN measurement in blood-derived DNA can identify genes widely relevant to non-blood phenotypes. This finding is consistent with a large body of work showing that mtDNA-CN measured in blood is associated with numerous aging-related phenotypes for which the primary tissue of interest is not blood (e.g.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A recently study found that 23blood-derived mtDNA CN is associated with gene expression across multiple tissues and is predictive for incident neurodegenerative disease, which provides evidence supporting the hypothesis that changes in mtDNA in whole blood may reflect metabolic health across multiple systems. 51 Second, though we accounted for confounders and known batch effects in mtDNA CN and harmonized metabolic traits, we still observed moderate to high heterogeneity in the association coefficients in meta-analysis of most of the phenotypes in both ancestry-specific analyses and across ancestries. Different distributions of age, sex, and phenotypes across study cohorts may partially explain the heterogeneity in these associations.…”
Section: Strengths and Limitationsmentioning
confidence: 82%
“…Similar results were reported for other neurodegenerative diseases (Filograna et al, 2020). Interestingly, although mtDNAcn derived from whole blood is often confounded by variation in cell type composition between individuals, a recent study found an association with AD suggesting that the mtDNAcn in whole blood could potentially reflect metabolic health across tissues (Yang et al, 2021). While the mtDNAcn overall seems to be reduced in brain regions affected by neurodegenerative diseases, mixed results have been reported for the effect of aging on mtDNAcn.…”
Section: Introductionmentioning
confidence: 99%